Immunohistochemical localization of calbindin-D28k in the kidney and cerebellum of the porcupines (Hystrix cristata) - Timurkaan, S; Aydin, A; Karan, M (Czech Academy Agricultural Sciences, 2003)
The localization of calbindin in the kidney and cerebellum of Hystrix cristata was investigated immunohistochemically using an antiserum against the 28k Da calbindin of chicken duodenum. Calbindin-D28k is an intracellular protein with a high affinity for calcium. This protein is exclusively localized in the distal convoluted tubules of the kidney and in Purkinje cells of the cerebellum. Functionaly, calbindin-D28k is supposed to be involved in the regulation of the reabsorption of calcium in the distal nephron, though the exact regulatory mechanisms are not yet known.
Keywords: calbindin-D28k; kidney; cerebellum; Hystrix cristata; immunohistochemistry